The Influence Of Digital Transformation And Financial Literacy On Msme Performance With Innovation As A Mediating Variable (A Study on MSMEs in Purwosari District) - Sari, Rindi Kartika; Choiruddin, Muhammad Nanang (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of digital transformation and financial literacy on MSME performance through innovation in Purwosari District, Pasuruan. Using a quantitative approach, data were collected from 100 MSMEs and analyzed with PLS-SEM. The results show that digital transformation directly improves MSME performance, whereas financial literacy has no direct effect. Both variables significantly enhance innovation, which positively affects performance and mediates their relationships with performance. These findings highlight innovation as a key mechanism for transforming digital capabilities and financial knowledge into business outcomes. Therefore, strengthening innovation capacity is essential for improving MSME competitiveness and sustainability.